1997
DOI: 10.1038/eye.1997.71
|View full text |Cite
|
Sign up to set email alerts
|

Cone erg subnormality to red flash in central retinal vein occlusion: A predictor of ocular neovascularization?

Abstract: were re-evaluated 6-55 months later to determine whether ocular neovascularisation had developed. Of the 21 CRVO eyes, 6 (29%) were subnormal to red in the affected compared with the normal fellow eye. At follow-up, all 6 (100%) patients had developed ocular neovascularisation compared with 1 (7%) of the 15 patients who were supernormal to red (p = 0.00013).Cone ERG subnormality to red flash in CRVO eyes compared with normal fellow eyes may be a predictor of later development of ocular neovascularisation.Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…1991a, 1991b; Johnson & McPhee 1993; Severns & Johnson 1993; Larsson et al. 1998a; Roy et al. 1998; Moschos et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1991a, 1991b; Johnson & McPhee 1993; Severns & Johnson 1993; Larsson et al. 1998a; Roy et al. 1998; Moschos et al.…”
Section: Introductionmentioning
confidence: 99%
“…Assessment of retinal nonperfusion by fluorescein angiography has been the standard method for classifying CRVO for a long time (Hayreh 1976;Laatikainen & Kohner 1976). However, because of difficulties in fluorescein angiographic evaluation and the definition of retinal ischaemia, several studies have shown that electroretinography (ERG) is a more suitable method to classify CRVO and predict ocular NV (Sabates et al 1983;Johnson et al 1988; Kaye & Harding 1988;Breton et al 1989;Sakaue et al 1989;Breton et al 1991aBreton et al , 1991bJohnson & McPhee 1993;Severns & Johnson 1993;Larsson et al 1998a;Roy et al 1998;Moschos et al 1999). Although most ERG responses change after CRVO, the implicit time is considered to be one of the best predictive parameters of ocular NV.…”
Section: Introductionmentioning
confidence: 99%
“…Roy et al 23 also studied the prognosis of CRVO eyes with supernormal cone ERG amplitudes elicited by red flashes. They reported that only 1 of the 15 patients (7%) who had supernormal cone ERGs developed ocular neovascularization, whereas all 6 patients with subnormal cone ERGs developed ocular neovascularization.…”
Section: Discussionmentioning
confidence: 99%
“…Supernormal cone responses (both a-and b-waves) in eyes with CRVO have been described in several papers. 21,22 This phenomenon has been reported to involve the long-more than the middlewavelength-sensitive cones but not the short-wavelengthsensitive cones or rods. 22 Supernormal cone responses in all 12 cases could be detected using red flash, although 4 of the 12 cases also showed supernormal cone responses to white flash.…”
Section: Erg In the Affected Eye (First Recordings)mentioning
confidence: 98%